Apparatus and method for alternative coatings applied to metals - Patents.com
Patent Information
- Application Number
- JP2022148001
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2015-09-15
- Filing Date
- 2022-09-16
- Publication Date
- 2025-01-09
- Estimated Expiration
- 2036-09-15
Smart Images

Figure 0007611198000021 
Figure 0007611198000022 
Figure 0007611198000023
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application is a continuation of U.S. Provisional Patent Application No. 62 / 218,870 (filed September 15, 2015). The benefit of which is claimed and is incorporated herein by reference in its entirety. background
[0002] Construction (e.g., roof and wall manufacturers), transportation (e.g., car and tractor truck manufacturers), manufacturers of railroad tracks), and the packaging industry (e.g. wine screw cap closures and saws) Many industries, including can manufacturers, use pre-printed metals such as stainless steel, tin, and aluminum. They use metals and plastics that have been processed to produce their final products.
[0003] Traditional solvent-based coatings and inks have flexibility, good elongation properties and scratch resistance. This is especially important for metal stock that requires bending, folding and / or stretching after coating. This is a useful property. The solvents used in these coatings have traditionally been highly volatile organic compounds. These solvents affect the rheological properties of the coating, e.g. viscosity. Used to control the degree of oxidation, allowing the coated product to be free of defects. High VOC The solvent also acts to dissolve or disperse contaminants on the precoated metal surface. This minimizes the effect of residual grease or dirt on the coating. This ensures coating uniformity and good adhesion. In addition, the solvent improves the smoothness, consistency, and wettability of the coating. , flow, solids set rate, and dry time.
[0004] Traditional high-VOC coatings cure or dry by solvent evaporation caused by heat and air convection. These solvent-based coatings are designed to be applied in such a way that the solvent is driven out of the liquid layer applied to the substrate. During the coating solidification process, organic solvents are released into the process air and VOCs occur in the exhaust gas stream and their use is subject to local, state and federal regulations. VOCs are classified as single compounds or as volatile ethers, acetic acid, acetic acid esters ... The mixture may include mixtures of acid salts, aromatic compounds, glycol ethers and aliphatic hydrocarbons. Manufacturers typically use rotor concentrators, regenerative catalytic oxidizers (RCOs), and regenerative thermal oxidizers. VOC control systems such as regenerators and refrigerants (RTOs) must be used. The system requires high initial capital costs and incurs ongoing operating costs. Administrative costs due to periodic analytical testing and inspection of the treated air stream exiting the control system; we incur ongoing costs, including reporting fees and penalties resulting from compliance issues;
[0005] Manufacturers are subject to regulations encouraging them to reduce or eliminate VOC emissions, so solvent-based coatings Instead of coatings, low-VOC and zero-VOC coatings are being developed. These alternative coatings are high solids, water-based, solvent-free liquid energy curing (UV ) and Electron Beam (EB)) and 100% for high temperature melt and powder coating applications These alternative coatings are commercially available and are available in a variety of forms, including 100% solids. It is used successfully in metal products that do not require extreme deformation. If readily available replacement coatings are applied to the metal prior to severe deformation, some coatings may be damaged. As a result of delamination, they typically lose adhesion to metals and / or themselves. These coatings have been shown to be Lack of elasticity means that the coating breaks down as the part becomes elongated, as in deep drawing processes. It has also been shown to be disruptive.
[0006] Furthermore, many conventional coatings are used on products that come into direct or indirect contact with food and beverages. When used in BPA is a chemical that can be used to protect food from bacteria and bacteria that can cause food poisoning by coming into direct contact with the metal surface of the can. It is a common component of metal can coatings applied to protect metal cans.
[0007] Apparently, when a food or beverage comes into direct contact with a packaging material, a measurable amount of the components of the packaging material is transferred to the food or beverage. may migrate into food and be ingested. This possibility of migration should be considered before marketing food packaging materials. The product will be evaluated by the Food and Drug Administration (FDA) as part of a transition review. The agency is a component of the FDA's Food Communication and Notification Program, which evaluates whether food is safe. .
[0008] BPA is commonly used in many food packaging materials, so it is important to limit its use to these applications. The increased interest in safe use is due to increased public awareness and scientific interest. As a result, many scientific studies have been published. Some of these studies The safety of ingesting low levels of BPA that migrate into food from food contact materials such as coatings It raises questions regarding.
[0009] Although the scientific data on the health effects of BPA is inconclusive, it has been linked to hormone imbalances, cancer, and In fact, the U.S. FDA has issued a strict FDA inspection of baby bottles, sippy cups, and other medical supplies to prevent heart problems. Food and Drug Administration to revoke approval for BPA-based materials in infant formula packaging The food additive regulations have been revised. Further precautions and regulatory measures are expected, so the food additive regulations for packaging materials are Removing BPA is a smart move. overview
[0010] An apparatus and method for replacement coatings applicable to metals is disclosed. In one embodiment, According to the invention, the device includes a composition having an ethylene acrylic acid copolymer, a neutralizing base, and water. The ethylene acrylic acid copolymer is from about 15 weight percent to about 45 weight percent of water. The device further comprises a metal coated with the composition.
[0011] Further features and advantages will become apparent from the following detailed description, taken in conjunction with the accompanying drawings which illustrate, by way of example, the features of various embodiments. This will become apparent from the detailed description. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 is a diagram illustrating an exemplary aluminum wine closure.
[0013] [Diagram 2] FIG. 2 illustrates an exemplary system for applying a coating to coiled metal according to one embodiment.
[0014] [Diagram 3] FIG. 3 illustrates an exemplary system for applying a coating to a metal sheet according to one embodiment.
[0015] [Figure 4A] FIG. 4A illustrates an exemplary system for applying ink to a metal sheet according to one embodiment.
[0016] [Figure 4B]FIG. 4B illustrates another exemplary system for applying ink to a metal sheet according to one embodiment.
[0017] [Diagram 5] FIG. 5 shows a chart comparing commercial oven curves of a water-based coating based on an EAA copolymer according to one embodiment versus a traditional solvent-based coating.
[0018] [Figure 6] FIG. 6 illustrates the Sutherland friction test ranking rating scale from 1 being the best to 4 being the worst according to one embodiment.
[0019] [Figure 7] FIG. 7 illustrates the Tabar adhesion test ranking rating scale from 1, best, to 6, worst, according to one embodiment.
[0020] [Figure 8] FIG. 8 illustrates a shell upper friction test ranking rating scale ranging from 1 (best) to 6 (worst) according to one embodiment.
[0021] [Figure 9] FIG. 9 illustrates a ranking rating scale for the 70 percent isopropyl alcohol rub test ranging from 1 being the best to 7 being the worst according to one embodiment.
[0022] [Figure 10] FIG. 10 shows the cure oven curve of a water-based coating applied using a commercial direct roll coating process according to one embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] The present disclosure provides a method for manufacturing a tungsten-based inkjet printer that can withstand rapid bending and extensive stretching after coatings and inks are applied. Coatings for metal parts (e.g., deep-drawn metal parts), including those requiring severe deformation Describes environmentally friendly flat metal coatings and inks along with coating and inking processes do.
[0024] The system and method produce coatings that contain little or no volatile organic compounds (VOCs). For deep drawing applications using coating and ink materials, functional or functional and decorative Coatings or coating / ink combinations are applied to metals (e.g. metal sheets, gold According to one embodiment, the system and method includes applying a coating to a beverage packaging Aluminum sheet metal used in the manufacture of deep drawn screw caps is coated on both sides. This includes applying a coating or a coating / ink combination. The combination of coatings and inks can be applied to any type of metal.
[0025] Briefly, in general terms, the various embodiments include ethylene acrylic acid copolymers, In one embodiment, the coating composition comprises an ethylene acrylate copolymer. The acid copolymer is from about 15 weight percent to about 45 weight percent of the total composition. In one embodiment, the ethylene acrylic acid copolymer is about 20.5 percent acrylic acid. The acrylic acid functional group may include from 25 to about 100 mole percent of the acrylic acid functional group being hydroxylated. It may be neutralized with ammonium hydroxide, potassium hydroxide or sodium hydroxide. It has been shown that other bases can also be used to neutralize the acrylic acid functionality. While the compositions may have many uses, in one embodiment the compositions are used in tie layer coatings, coatings for coatings, and the like. Coating, overvarnish coating or inside for screw cap manufacturing Used as a primary coating to form a lacquer coating.
[0026] In a particular embodiment, about 25 mole percent of the acrylic acid functional groups are dissolved in ammonium hydroxide. However, in other embodiments, 100 mole percent of the acrylic acid functional groups are reacted with In another embodiment, the functional group is reacted with ammonium hydroxide and water. Sodium oxide is used to neutralize about 25 to about 100 mole percent of the acrylic acid functional groups. In addition, about 25 to about 70 mole percent of the The acrylic acid functionality of the compound can be reacted with ammonium hydroxide and sodium hydroxide. In a preferred embodiment, ammonium hydroxide is present at about 30 mole percent of the acrylic acid functional groups. The sodium hydroxide neutralizes about 40 mole percent of the acrylic acid functionality. In another embodiment, ammonium hydroxide is used to neutralize about 2 of the acrylic acid functional groups. 5 to about 70 mole percent of about 0 to about 100 percent neutralized. 0 percent water When acrylic acid is neutralized with ammonium oxide, 25 to 70 mole percent of ammonium oxide is used. The acrylic acid functionality is neutralized using only sodium hydroxide. When ammonium is used to neutralize the acrylic acid functional group, sodium hydroxide Not used.
[0027] In yet another embodiment, the composition comprises ethylene glycol at a concentration of about 15 weight percent in water. The ethylene acrylic acid copolymer dispersion may also include an ethylene acrylic acid copolymer dispersion. It may also be at a concentration of about 45 weight percent in water. The carboxylic acid copolymer may be Primacor 5980I. About 35 percent to about 45 percent of the acrylic acid functional groups of Cor 5980I are water-soluble. It may be neutralized with sodium hydroxide or potassium hydroxide.
[0028] In one embodiment, the composition comprises between 1 and 70 percent by weight of pigment to enamel. The pigment may include a concentration of ethylene acrylic acid copolymer.
[0029] In other embodiments, the composition comprises between 1 and 50 weight percent water. The wax may include a wax having a concentration of ethylene acrylic acid copolymer to the wax. Carnauba wax may be used, and carnauba wax may comprise about 1% of the total coating solids. It may be at a concentration of 0 weight percent.
[0030] Another embodiment disclosed herein is a method of forming a composition. The method includes: The ethylene acrylic acid copolymer is mixed with water at a concentration of 15 to 45 weight percent, and the ethylene acrylic acid copolymer is mixed with water at a concentration of 15 to 45 weight percent. The acrylic acid copolymer / water mixture is heated with a base to convert 25 to 10% of the acrylic acid functionality. In one embodiment, the mixture is heated to 110° C. do.
[0031] The method also includes mixing the pigment with an ethylene acrylic acid copolymer dispersion at a concentration of 1 to 70 weight percent. The pigment may be mixed with an ethylene acrylic acid copolymer at a pigment concentration of 100%. In one embodiment, the method comprises mixing the wax with the ethylene acrylic acid copolymer dispersion in one or more Blending the wax at a concentration of 50 weight percent with ethylene acrylic acid copolymer may include.
[0032] In one embodiment, the ethylene acrylic acid copolymer has a content of about 20.5 weight percent. Further, the method of making the dispersion comprises the steps of: 25 to 100 mole percent of acrylic acid functionality with any combination of sodium In a preferred embodiment, ammonium hydroxide neutralizes about 30 of the acrylic acid functional groups. The sodium hydroxide neutralizes about 40 mole percent of the acrylic acid functionality. Neutralize.
[0033] Yet another embodiment disclosed herein relates to a method for coating a metal substrate. In one embodiment, the method includes coating a metal substrate with a first coating composition. the first coating composition comprising 25 to 100 mole percent acrylic acid functionality Ethylene oxide in water at a concentration of 15 to 45 percent by weight produced by neutralizing The method also includes subjecting the mixture to an ambient temperature of about 75° F. (about 2 By heating a metal substrate from 3.9°F (approximately 37.8°C) to 100°F (approximately 37.8°C) in 5 seconds, and curing the first coating composition on the metal substrate. The first coating composition on the metal substrate is heated to an ambient temperature of about 75° F. It is hardened by heating the metal substrate to 250°F for 120 seconds. Other temperatures and times may be used for the curing process.
[0034] In one embodiment, the method includes coating the metal substrate with a second coating composition. The second coating composition may include a 25 to 30% acrylic acid functional group. A concentration of 15 to 45 weight percent produced by neutralizing 100 mole percent Ethylene acrylic acid copolymer dispersion in water at 100°C and and a pigment having a concentration of between 1 weight percent and 70 weight percent.
[0035] In another embodiment, the method includes coating the metal substrate with a third coating composition. The third coating composition may include a 25 to 40% acrylic acid functional group. 15 to 45 weight percent produced by neutralizing up to 100 mole percent Ethylene acrylic acid copolymer dispersion in water at a concentration of 1.0001 and 1.0001 Wax having a concentration of between 1 and 50 weight percent wax Includes.
[0036] Another embodiment of the method is to provide a coating composition that is free of volatile organic compounds (VOCs). The method includes coating a metal substrate with
[0037] Another embodiment of the method is to provide a method for treating a patient having a BPA non-intent (NI) state. The method includes coating a metal substrate with the coating composition.
[0038] To address the shortcomings of conventional solutions, alternative coatings and and coating / ink combinations, as well as environmentally friendly solvents (zero or very low). Extremely low VOC or solvent-free (zero VOC) coatings and coating / ink combinations Damaging coatings or coatings / inks on metal surfaces using While retaining the bend, fold, and stretch capabilities of metal, alternative coatings and Applying the coating / ink combination to metals (e.g., metal sheets and metal coils) Here's how:
[0039] FIG. 1 illustrates an exemplary aluminum wine closure 18 according to one embodiment. Each aluminium wine closure may have dimensions of 30mm diameter x 60mm length. The metal is then deep-drawn onto a flat metal sheet that has previously been coated on both sides with a solvent-based coating. It can be formed by:
[0040] Coatings are applied to metal substrates using a coil or flat sheet coater. An exemplary system for applying a coating to a coil of metal is shown. The metal substrate 20 is supplied in a coil form to the coil coater process 24. The web is unwound at 26 and passed through an inlet accumulator 28 for steady delivery to the coating train. The non-coiled metal substrate 20 is then passed through a pre-treatment station 30. There, the metal surface is cleaned and optionally treated to increase its surface energy. , and optionally coated with a tie coating such as a size or base coat. If the metal is coated with a tie coat, it is dried in drying station 32 and then The wire is then fed to a coil coater 24 which applies a primary color or functional coating to the metal. The main coater station 34 applies a coating to the substrate. The functional coating is cured in a curing oven 36. The top coat of the coil coater 24 is then At station 38, protective over-varnish is applied. A topcoat such as a teflon-based teflon coating is applied to the metal substrate and cured in a finishing oven 40. The substrate then enters a water cooling station 42 to quickly cool the coated metal, after which , allowing the coated metal to be continuously unwound at the proper tension and unwinding speed. The fuel enters the accumulator 44 .
[0041] Coating The coating process is carried out in one or more passes on one or both sides of the metal substrate. Multiple coating layers can be applied. FIG. 3 shows a metal sheet coated with a coating according to one embodiment. 3 shows an exemplary system for applying a coating to a metal sheet 50. The metal sheets may be stored in a sheet or plate feeder 52. The sheets 50 are fed onto a conveyor (not shown). Before being coated, the substrate is cleaned and treated to increase its surface energy (not shown). During application of the coating, the sheet is supported underneath by a pressure roller 56. As shown in FIG. 3, the conveyor moves the metal sheet into operation at the base coater 58. Here, the metal sheet 50 is fed between a coating roller 54 and a pressure roller 56. The coating tray 60 transfers the coating material to the application roller 54 using a series of rollers 62. A transfer coating roller applies the coating to each metal sheet as it passes. After the base coater 58 has been applied, the metal sheet 50 is transferred to a wicket oven 64. This is a machine that holds individual metal sheets and transports them through the oven at a set speed. The coated metal sheet is then heated in a wicket oven 64 at a predetermined temperature. The sheets are heated, dried, and cooled in the oven and then transferred to a sheet or plate stacker 68. can be.
[0042] The coating is a liquid, which is applied for decorative, functional or decorative and functional purposes. Binders, pigments, dyes applied to the inside and / or outside of the substrate (e.g. aluminum metal) The coating may include, but is not limited to, a wax or a coating. It may be applied using a complete coverage technique, or it may be applied to specifically cover selective portions of the substrate. These include a tie layer coating, which is transparent and relatively The coating composition includes a basecoat, which includes a coating having a substantially low pigment content, and a subsequent coating. They are applied to aid in adhesion of the coating to the metal and also to colour coatings for decorative purposes. Coatings and overcoats to protect color coats and printed artwork Includes varnish coating.
[0043] Coatings applied to the interior and exterior surfaces of metal packaging components are used to They can have different functions depending on the application. For example, metal packaging that comes into direct contact with food The internal coating on the housing components protects the metal from corrosion by food contents and Protects food from contamination. The internal coating also contains agents that aid in the functionality of the final product. For example, to reduce the torque required to remove a cap from a bottle, In the case of screw cap closures, a slip agent such as wax may be used. The exterior coating is applied for decorative purposes and to protect the package or package components from corrosion. It is applied to protect the substrate and the printed design from scratches and scuffs.
[0044] The ink is applied either directly to the metal or in a sheet-fed offset lithography printer. It is applied to a flat metal sheet over a coating that has been previously applied to the metal using a linter. 4A and 4B show an exemplary system for applying ink to a metal sheet. In offset printing, the metal is transferred from a plate to a blanket, which then prints the metal. These systems consist of an inked image that is transferred to a surface. Lithography process using hydrophobic inks and aqueous jetting solutions applied to an image carrier. The ink is supplied to the image carrier via a roller together with the liquid for ejection. The non-printing areas of the image carrier are covered with ink to keep the non-printing areas free of ink. The ink is applied to the surface of the cured coating to attract the jetting solution, which repels the solid. Color or decorative elements can be applied to the metal. These inks cure to a clear overcoat. Can be protected by overcoating with a bar varnish coating .
[0045] As shown in FIG. 4A, metal sheets 70 are stored in a sheet or plate feeder 72. From the sheet feeder 72, each metal sheet 70 is fed onto a conveyor (not shown), The blanket cylinder 7 is then fed to a lithographic coater 73. 4, and a pressure roller 76 is located on the opposite side of the conveyor of the lithography coater 73. The blanket 77 transfers the ink through a series of rollers to the blanket cylinder 74. As shown in FIG. 1, the conveyor transports the metal sheet to a lithographic coater 73 where the metal sheet is The blanket cylinder 74 and the pressure roller 76 are connected to the blanket cylinder 74 and the pressure roller 76. The roller 74 applies a coating to each metal sheet as it passes over the conveyor. After receiving the inked image at the lithographic coater 73, the metal sheet 50 is conveyed to both ends of the conveyor. The coating material can be fed to an over-varnish coater 78 that includes a coating roller 80 and a pressure roller 82 on the side. A varnish tray 84 for storing overvarnish is applied to the coating roller via a series of rollers 86. The varnish is then applied to the metal sheet via the application roller 80. After receiving the varnish, the coated metal sheets are attached to a wire that holds the individual metal sheets. The coated metal sheet is fed to a wicket oven 88 containing a wicket 90. The sheets are then dried in a hot oven 88 and then transferred to a sheet or plate stacker 92.
[0046] As shown in the embodiment of FIG. 4B, the metal sheet 100 is An impression cylinder 102 on one side and an offset cylinder on the other side of the metal sheet 100 104 to the offset printing assembly. The ink applicator may also be used to assist in feeding the metal sheet to the printing assembly. 108 transfers ink through a series of rollers to a plate cylinder 110 as shown in FIG. 4B. A water tray 112, which stores water (or a composition containing water), is transported by a series of rollers 114. Water is applied to the plate cylinder 110 through the plate cylinder 110. From the plate cylinder 110, the ink The metal sheet 100 is transferred to the offset cylinder 104. When the offset cylinder 104 is between the metal sheet 100 and the set cylinder 104, the offset cylinder 104 The ink coating is applied to the metal sheet 100 as it passes through the offset printing assembly. Similar to the previous embodiment illustrated in FIG. 4A, the metal sheet containing the inked image is The coated substrate may then be sent to a burner varnish coater and then to an oven for curing.
[0047] The system includes one or more desired coatings and coating / ink combinations. Such properties include reduced curing energy, shortened curing time, and reduced cost. Strong adhesion to metals, good solvent rub resistance, good abrasion resistance, highly flexible, over 250% The stretchability that can be achieved, acceptable blocking resistance in real-world environments, and unintentional BPA ( The system includes, but is not limited to, precoat and non-precoat conditions. This can include a metal treatment step to remove hydrophobic contaminants and to prevent direct flame, Surface treatment by means of, but not limited to, ozone, corona, and / or plasma. The system may also include a coating application step, These include roll, reverse roll, gravure, dry offset, wet offset, slot die, It features curtain, knife, rod, pressure rod and spray coater technology. The system may further include, but is not limited to, a post-coating curing step. This includes, but is not limited to, environmentally friendly removal of solvents, e.g. , water with forced convection, forced convection heated air, induction heating, induction heating combined with forced ventilation , IR Energy, Radio Frequency, and Forced Ventilation Combined with IR Energy, Radio Frequency, and Forced Ventilation Furthermore, the system is applied to the cured water-based coating. The ink printing process may include a UV ink printing process for decorating the surface. These include, but are not limited to, lithography, flexography, inkjet, xerography, and gravure. The ink curing process may include, but is not limited to, mercury vapor lamps, iron dopant lamps, etc. The radiation emitted from mercury vapor lamps, gallium-doped mercury vapor lamps, fluorescent lamps, and LEDs Examples of light sources that can be used for this purpose include, but are not limited to, UV light, which can
[0048] This technology uses lower VOCs than traditional high-solvent coatings and inks. This results in environmentally friendly coatings and inks that require less energy and curing times. An example of this improved curing efficiency for applying a coating can be seen in Figure 5. Here, we compare the technology disclosed herein (water-based coating) with conventional solvent-based coating. The system is compared to a commercial oven curve.
[0049] Metals coated and decorated using the techniques described herein work well on flat sheets. It has excellent performance characteristics for demanding deep drawing applications. The cured coating can be designed to have a BPI-NI state.
[0050] According to one embodiment, a first aqueous coating composition is provided. Contains acrylic acid (EAA) copolymer, neutralizing base, and deionized or softened water. Pellets The solid EAA copolymer in the form of 1,2-dichloro-1,2,4-tetramethylphenylacetamide is stirred in heated water containing a base. The base, which may contain carboxylic acids, reacts with the desired percentage of the carboxylic acid groups of the EAA copolymer. Various relative amounts of EAA, base, and water were added in predetermined concentrations to the mixture. Appropriate dispersion temperature is used to improve the resulting aqueous coating properties (EAA particle size and composition). For example, neutralization of acrylic acid is changed from 30 to 70 mol / L. The concentration of EAA copolymer in water was varied from 20 to 43 weight percent (mixing strength and By changing the temperature to 15-450 nm, the average particle size and the dispersion temperature were kept constant. A stable EAA dispersion was formed having a viscosity of 5 to 3,000,000 cp. The resulting aqueous dispersions can be tailored to perform optimally in various coating application processes. It is possible.
[0051] The resulting EAA coating adheres strongly to aluminum but not to itself. This property of EAA coatings is well known and is one of their major industrial uses. This is why one of the reasons is that it is a heat seal coating. Adhesion of the individual sheets to each other is undesirable. In sheet metal coating applications, this property is known as "blocking." Blocking occurs when adjacent aluminum sheets in the stack are blocked. In effect, the sheets bond together, making commercial processing difficult. The disclosed process is a step in the manufacture of coatings. Within a stack of flat sheets, with varying pre-processing and coating application conditions This problem is addressed by direct modifications to the coatings of the layers that contact each other.
[0052] EAA coated flat plates can be used to modify appearance or performance characteristics depending on the requirements of the finished part. The sheet metal is coated with a single coating that may contain other additives such as pigments or waxes. It is possible to do this.
[0053] EAA coatings can be used as a single coat, but the technique can also be used with multiple coats. Suitable for transparent size coating or for metallic or decorative color requirements. A tie layer consisting of a "lightly" pigmented base coat may be required. If a transparent size is required and does not adhere well to the metal, a first EAA dispersion may be used. A coating can be applied and film-formed onto the metal first. This coating is , aluminum and any number of compatible pigments, e.g., color coatings. The coating is designed to adhere strongly to a second coating of EAA dispersion No. 1. In addition, if the color coating needs protection or causes blocking defects If there is a tendency for the third coating to be applied, this coating must be applied with a matching The first EAA coating may be mixed with a metal oxide dispersion. The food contact side of the is made of BPA-N blended with food contact approved pigments and / or waxes. I EAA coating for integrated packaging processing efficiency or performance can be improved.
[0054] Another embodiment is a method for printing on an EAA coating applied to a flat metal. This involves the use of cationic UV inks. Free radical UV coatings are Although not generally known to have the necessary extendibility properties for use, the inventors have The mer / monomer system is added to the EAA coating prior to and during the metal extension process. Free radical UV coatings can be used successfully if they are designed to adhere strongly to the coating. In fact, a properly formulated UV ink can be used to produce a highly oriented EAA coating. This allows the material to "ride" the drawing and function in deep drawing applications. When used, the size coating, base coating, or primary color coating is To add overall color coverage or selective artwork prior to squeezing, 100% solid UV ink for flood printing or spot printing. This technique allows metal to be distorted so that the image appears after it has been distorted, such as in deep drawing applications. This may include printing of special artwork (distortion printing) designed to
[0055] According to one embodiment, commercially available water-based coatings, such as Michelma n 4983R (Ethylene acrylic acid copolymer dispersion), Michelman P18 53 (ethylene acrylic acid copolymer dispersion), Michelman 4983RHS ( High solids, large particle size version of Michelman 4983R), Michelman MDU 20 (Proprietary Polymer Dispersion), Dow Adcote 37P295 (Ethylene Vinyl acetate copolymer dispersion), Dow Adcote 37-220 (ethylene copolymer) BASF Joncryl 60 (styrene acrylic resin) ammonia solution), BASF Joncryl 74A (acrylic copolymer emulsion) ion), BASF Joncryl 77 (acrylic copolymer emulsion), BAS F Joncryl 89 (acrylic copolymer emulsion), BASF Joncryl yl 1695 (acrylic copolymer emulsion), DOW HYPOD™ 85 03 (high molecular weight polyolefin dispersion), DOW HYPOD™ 1001 (polymer polyolefin dispersion), and DOW HYPOD™ 9105 (high molecular weight polyolefin The resin dispersions are intended for application alone or in combination to flat sheet or coiled metal. Can be used as a coating.
[0056] According to one embodiment, an ethylenediamine having an acrylic acid content of about 20.5 weight percent. The water-based coating is made using acrylic acid copolymer. The solid EAA pellets are mixed with Ammonium hydroxide is used to neutralize 25 to 100 mole percent of the acrylic acid functionality. in deionized water at a concentration of between about 15 and 45 weight percent. The mixture is stirred at about 110°C (although it can be heated to about 85°C to 140°C). The resulting EAA dispersion is then heated to 150° C. The resulting EAA dispersion is then used as a primary coating for application to flat sheet or coil metal. Used as a cover.
[0057] In one embodiment, the aqueous coating comprises in the range of 19.5 to 21.5 weight percent The polymer is made using an ethylene acrylic acid copolymer having an acrylic acid content. In the form, solid EAA pellets were dissolved in deionized water at a concentration of 45 weight percent with hydroxyethyl ammonium hydroxide. Mix with ammonium to neutralize 25 mole percent of the acrylic acid functionality. Heat to 110°C under stirring. The resulting EAA dispersion is applied to flat or coiled metal. It is used as a primary coating to
[0058] In another embodiment, the ethylene glycol esters have an acrylic acid content in the range of about 20.5 weight percent. A water-based coating is made using a propylene acrylic acid copolymer. Solid EAA pellets were mixed in deionized water at a concentration of 15 weight percent and heated to 110° C. with stirring. 100 mole percent of the acrylic acid functionality is neutralized with ammonium hydroxide. The resulting EAA dispersion is used as a primary coating for application to flat sheet or coil metal. will be done.
[0059] According to another embodiment, the water-based base and color coatings comprise from 1 to 70 weight percent The appropriate pigment to EAA copolymer solids concentration is about 19.5 to 21.5 weight percent. EAA dispersions produced using EAA pellets mixed with acrylic acid at 100% water The mixture contains 20 to 43 weight percent EAA in deionized water, and converts the acrylic acid functionality to hydroxyl. The EAA dispersion is neutralized with ammonium chloride at 30 to 70 mole percent. is used as a base or color coating for application to flat sheet or coiled metal. It is used.
[0060] According to another embodiment, the water-based protective overvarnish coating has a viscosity of 19.5 to 21. EAA aqueous solution made using EAA pellets with 5 weight percent acrylic acid In the dispersion, a range of 1 to 50 weight percent wax to total EAA copolymer solids is The acrylic acid functional group is mixed in deionized water at a concentration of 20 to 43 weight percent. The product is neutralized with ammonium hydroxide at 30 to 70 mole percent. The EAA dispersion is applied to the block on the coated flat metal sheet or coil. Used as a protective varnish coating to minimize the possibility of cracking.
[0061] According to another embodiment, the acrylic acid content is between 19.5 and 21.5 weight percent. The water-based coating is made using ethylene acrylic acid copolymers. The pellets were dissolved in 25 weight percent EAA in deionized water with ammonium hydroxide and hydroxide hydrate. sodium to neutralize 70 mole percent of the acrylic acid functionality, 40 mole percent of the acrylic acid functional groups were neutralized with acrylic acid, and the remaining 30 mole percent Use ammonium hydroxide to neutralize the mixture. Heat the mixture to 110°C with stirring. The resulting sodium ionomer EAA dispersion is then coated onto a flat metal or coil for application. It is used as a primary coating for
[0062] According to another embodiment, the water-based systems and color coatings contain a suitable pigment in an amount of 1 to 70 The EAA pellets (2 About 20.5 weight percent acrylic acid mixed with 5 to 40 weight percent EAA and 30 to 70 mole percent with ammonium hydroxide and sodium hydroxide. EAA aqueous dispersions formed using acrylic acid functional groups neutralized with ethylene glycol acrylate (EEA). The sodium hydroxide was mixed into the neutralized solution. 70 mole percent is used to neutralize 0 to 100 percent. AA sodium ionomer dispersions are used as a base or coating for application to flat or coiled metal. is used as a color coating.
[0063] According to another embodiment, the water-based protective overvarnish coating comprises a compatible wax: EAA phenols were used in concentrations ranging from 1 to 50 weight percent wax to total coating solids. 19.5 to 20 weight percent EAA mixed with deionized water. 1.5 weight percent acrylic acid and ammonium hydroxide and sodium hydroxide. (having acrylic acid functionality neutralized by 30 to 70 mole percent with ammonium) The sodium hydroxide was mixed into the EAA aqueous dispersion prepared by the method described above. To neutralize 0 to 100 percent of the total neutralized 30 to 70 mole percent The resulting EAA sodium ionomer dispersion is used to coat flat surfaces. Protective varnish coating to minimize the possibility of blocking on flat metal sheets or coils It is used as a feeding.
[0064] According to a preferred embodiment, the water-based protective overvarnish coating is The wax solids are added to the EAA copolymer in an amount of 1 to 50 weight percent of the total EAA copolymer solids. EAA pellets (20 to 30 weight percent EAA mixed with deionized water) were used in a range of concentrations. 19.5 to 21.5 weight percent acrylic acid combined, and ammonium hydroxide Acrylic acid functional groups neutralized with 65 to 75 mole percent of acrylic acid and sodium hydroxide. The compound is prepared by mixing the compound with an aqueous dispersion of EAA prepared using a tertiary amine functional group. Sodium hydroxide accounts for 50 to 70 percent of the total 65 to 75 mole percent neutralized. The resulting sodium EAA ionomer dispersion is used to neutralize the coating. Protective wrapping to minimize the possibility of blocking of coated flat metal sheets or coils. Used as a varnish coating.
[0065] According to a particular embodiment, the wax used in the protective overvarnish is carnauba or In another embodiment, the wax used in the varnish may be oxidized high density polyethylene. The oxalate is a fatty acid amide or bisamide, a montanic acid ester, a microcrystalline, a paraffin, an oxide It may be low density polyethylene or Fischer-Tropsch wax. The compounds may be used alone or in combination.
[0066] In certain embodiments, the metal to be coated may be in coil or sheet form. In certain embodiments, the metal is flame-cleaned to remove any residual surface contaminants immediately prior to coating. Metals can also be treated with a plasma prior to coating to remove Modify its surface energy by using thermal, ozone, or corona treatment. It may be processed for this purpose.
[0067] In a particular embodiment, the metal may be aluminum, such as 8011 alloy.
[0068] In a particular embodiment, the coating is performed using a direct roll coater, a reverse roll coater, or a combination of both. -, rod coater, pressure rod coater, spray coater, slot die coater, Or it can be applied to coil or sheet metal using a curtain coater.
[0069] According to one embodiment, the coating has a viscosity of about 0.25 milligrams per square inch (6.45 It can be applied at a rate of 100 mg / sq. cm (2.5 sq. cm) to approximately 15 mg / sq. in (6.45 sq. cm). As used in this disclosure, "about" or "approximately" means within 10 percent of a given amount. Furthermore, color coatings can be applied directly to metal surfaces or as transparent coatings on metal surfaces. (size coating) or lightly pigmented (base coating) tie layer. In one embodiment, the color layer can be protected by a varnish coating.
[0070] In a particular embodiment, the coating dryer includes a wicket transport system for the metal sheet. A forced convection oven is used in which the system or sheet remains flat. It may also be a combination.
[0071] In certain embodiments, an infrared heating system with forced air convection or a forced air convection system is used. Induction heating system having a flow, in which a metal sheet is conveyed through a wicket conveying system. As known in the art, the sheet is transported using a Alternatively, other drying systems may be used.
[0072] During the coating drying process, the metal (e.g., aluminum) coil or sheet is From an ambient temperature of about 75°F (23.89°C) to about 100°F (37.78°C) in the It can be heated to a temperature of 500° F. (260° C.). In a preferred embodiment, the aluminum The aluminum coil or sheet is heated from ambient to approximately 150°F (65.56°C) in an oven. Heat to a temperature of about 250°F (121.11°C). Aluminum coil or sheet The material can be heated from ambient temperature to the desired final temperature in about 5 to 120 seconds. In one embodiment, the aluminum coil or sheet is heated to the desired temperature in 20 to 80 seconds from ambient temperature. is heated to a temperature of
[0073] In a particular embodiment, an aluminum coil or sheet is coated with a water-based polymer. The substrate may be overprinted with free radical or cationic UV inks. . Example 1: Primary EAA Coating Production
[0074] 2 liter Parr series 4520 benchtop stirred reactor with quartz window for viewing The EAA dispersion was prepared using a flask.
[0075] 425 grams of Primacor 59801EAA (The Dow Chemical al Company, 2030 Dow Center, Midland, MI486 74), 1220.4 grams of deionized water, 54.6 grams of aqua ammonia 28 parts Cent Item 511561-1 (Hi Valley Chemical, 1134W 850N, Centerville, UT84014) (Measure specific gravity at 60F, weight Converting it to percent ammonia gave it a value of 25.7 percent. The actual content was added to the reactor to produce 1700 grams of dispersion. Assemble the vessel, close the vent, place in a heating mantle, and allow the reaction to reach 60-80°C. Heat with mixing at 450-500 rpm until the mixture is fully combined, at which point the mixing speed is reduced to 675 rpm. The temperature was allowed to continue to increase to 110°C with constant stirring and the reactor vent was closed. The batch was held at 110°C for 1 hour to disperse all of the EAA.
[0076] After the EAA is completely dispersed, remove the heating mantle and increase the stirring speed to 300-450 rpm. Water at 20-26°C was added inside until the EAA dispersion temperature dropped to 28-35°C. Cooling was initiated by passing it through a cooling coil. The reactor was then evacuated and the dispersion was cooled to 100° C. The EAA dispersion was poured into a stainless steel beaker and degassed while cooling to room temperature. The dispersion was passed through a 0.8 mm stainless steel strainer into a polyethylene storage container. was semi-transparent. Example 2: Primary EAA Sodium Ionomer Coating Preparation
[0077] 2 Liter Parr Series 4520 Benchtop Stirred Reactor with Quartz Window for Viewing The sodium EAA ionomer dispersion was prepared using a centrifuge.
[0078] 435.4 grams of Primacor 5980I EEA (The Dow Chemical mical Company,2030 Dow Center,Midland,MI 48674), 1201.5 grams of deionized water, 24.5 grams of aqua ammonia 2 8 percent Item 511561-1 (Hi Valley Chemical, 11 34W850N, Centerville, UT84014) (Measure specific gravity at 60F By converting it to weight percent ammonia, it was found to be 25.7 percent. (actual content shown) and 38.6 grams of sodium hydroxide, 50 percent solution. Liquid, manufacturing code 110014 (Brenntag Specialities Inc. ,Camino Sobrante #215,Orinda,CA 94563) The reactor was assembled and vented. Close the cover and place in a heating mantle for 450-500 rpm until the reaction reaches 60-80°C. The mixture was heated while mixing at 400 rpm, at which point the mixing speed was increased to 675 rpm. The temperature was increased to 110° C. with continued stirring and the reactor vent was closed. It was held at 0° C. The temperature was increased for 1 hour to allow all the EAA to disperse.
[0079] After the EAA is completely dispersed, remove the heating mantle and increase the stirring speed to 300-450 rpm. Water at 20-26°C was added inside until the EAA dispersion temperature dropped to 28-35°C. Cooling was initiated by passing it through a cooling coil. The reactor was then evacuated and the dispersion was cooled to 100° C. The mixture was poured into a steel beaker and degassed while being cooled to room temperature. After about 24 hours, the EAA dispersion The liquid was passed through a 0.8 mm stainless steel strainer into a polyethylene storage container. The appearance of the dispersion was translucent. Example 3: Michelman 4983R - White Beige Coatings Manufacturing
[0080] Michem® Prime 4983R (Michelman, Inc., 9080 Shell Road, Cincinnati, Ohio) 95 grams of dispersion Uline (Part Number S-19520) 1 / 2 Pint (0.24 Liter) Tin Can Using a pipette, 5 grams of Sun Chemical (WH D-9507)”Sunsperse White 6”(Sun Chemical Corporation,35 Waterview Boulevard,Parsi Co., Ltd., NJ 07054) was weighed into the dispersion. Cole-Parmer fitted with a 30mm diameter 316 SS axial impeller Mix the coating and pigment dispersion together using a mixer (Model #50006-01). The mixing speed was gradually increased from 700 rpm to 2000 rpm. Once 0 rpm was reached, mixing was continued for an additional 60 seconds. The can was then fitted with a tinned steel lid. Used and closed for storage. Example 4: Primary EAA-White Base Coating Production
[0081] 95 grams of the EAA dispersion prepared in Example 1 was diluted with Uline (part number S-19520) The mixture was weighed into a 2 pint (0.24 liter) tin-plated steel can. Using a pipette, 5 grams Sun Chemical (WHD-9507) "Sunsperse White 6”(Sun Chemical Corporation,35 Waterview Boulevard, Parsippany, NJ07054) was weighed into the dispersion. Immediately fitted with a 30mm diameter 316 SS axial impeller set at 700 rpm. Using a combined Cole-Parmer mixer (Model #50006-01), The coating and pigment dispersions were mixed together. The mixing speed was adjusted from 700 rpm to 2000 rpm. The speed was gradually increased to 2000 rpm. Once it reached 2000 rpm, mixing was continued for an additional 60 seconds. The cans were then closed for storage with tinned steel lids. Example 5: Primary EAA Sodium Ionomer - White Base Coating Production
[0082] 95 grams of the EAA dispersion prepared in Example 2 was dissolved in Uline (part number S-19520) The mixture was weighed into a 2 pint (0.24 liter) tin-plated steel can. Using a pipette, 5 grams Sun Chemical (WHD-9507) "Sunsperse White 6”(Sun Chemical Corporation,35 Waterview Boulevard, Parsippany, NJ07054) was weighed into the dispersion. Immediately fitted with a 30mm diameter 316 SS axial impeller set at 700 rpm. Using a combined Cole-Parmer mixer (Model #50006-01), The coating and pigment dispersions were mixed together. The mixing speed was changed from 700 rpm to 2000 rpm. The rpm was gradually increased to 2000 rpm. Once it reached 2000 rpm, mixing was continued for an additional 60 seconds. The cans were then closed for storage with tinned steel lids. Example 6: Michelman 4983R - Color Coating Production
[0083] 87 grams of Michem® Prime 4983R EAA dispersion was added to Uli ne (Part No. S-19520) 1 / 2 pint (0.24 liter) tin-plated steel can with scale Using a pipette, 13 grams of Sun Chemical (BPD-0015 )”Sunsperse Blue 15:3”(Sun Chemical Corp oration,35 Waterview Boulevard,Parsippan y, NJ07054) was weighed into the dispersion. Immediately, a 30-minute stirrer set at 700 rpm was Cole-Parmer mixer fitted with a 316 mm diameter SS axial impeller ( Model #50006-01) to mix the coating and pigment dispersions together. The mixing speed was gradually increased from 700 rpm to 2000 rpm. Once this is reached, mixing is continued for an additional 60 seconds. The cans are then stored with tinned steel lids. Closed to. Example 7: Primary EAA-color coating production
[0084] 87 grams of the EAA dispersion prepared in Example 1 was diluted with Uline (part number S-19520) The mixture was weighed into a 2 pint (0.24 liter) tin-plated steel can. Using a pipette, 13 grams of Sun Chemical (BPD-0015) "Sunsperse Blue 15:3”(Sun Chemical Corporation,35 Waterv iew Boulevard, Parsippany, NJ07054) was weighed into the dispersion. Immediately, a 30mm diameter 316 SS axial impeller set at 700 rpm was A Cole-Parmer mixer (Model #50006-01) was used to The coating and pigment dispersions were mixed together at 200 rpm. The mixing speed was reduced from 700 rpm to 20 The rpm was gradually increased to 2000 rpm. Once 2000 rpm was reached, mixing was continued for an additional 60 seconds. The cans were then closed for storage with tinned steel lids. Example 8: Primary EAA Sodium Ionomer - Color Coating Production
[0085] 87 grams of the EAA dispersion prepared in Example 2 was dissolved in 1 / 2 mL of Uline (part number S-19520). The mixture was weighed into a 2 pint (0.24 liter) tin-plated steel can. Using a pipette, 13 grams of Sunsperse Blue 15:3, BPD-0015 (Sun Che mical Corporation,35 Waterview Boulevard , Parsippany, NJ 07054) was weighed into the dispersion. Cole-P fitted with a 30mm diameter 316 SS axial impeller set at 1000m Coatings and pigments are processed using the Armer mixer (Model #50006-01). The dispersions were mixed together. The mixing speed was gradually increased from 700 rpm to 2000 rpm. Once 2000 rpm was reached, mixing was continued for an additional 60 seconds. The can was then tinned. A steel lid was used to close for storage. 9: Preparation of Carnauba Wax Dispersion
[0086] 550 grams of "GC-704 CWE Carnauba WAX Emulsio n” (Green Chem Coatings, Bishop, GAME) 1200 10 mL Vollrath stainless steel beaker and stirred at 400 rpm at ambient temperature. 330 grams of deionized water was slowly added to obtain a stable 25 percent solids calcium carbonate solution. The dispersion was mixed for 60 seconds at ambient temperature and then diluted with 0.8 The mixture was passed through a 0.05 mm stainless steel strainer into a polyethylene container for storage. Example 10: Primary EAA-Overvarnish Coating Preparation
[0087] 90 grams of the EAA dispersion prepared in Example 1 was diluted with Uline (part number S-19520) The mixture was weighed into a 2 pint (0.24 liter) tin-plated steel can. 10 g of the "carnauba wax dispersion" prepared in the above was weighed into the dispersion. Col fitted with a 30mm diameter 316 SS axial impeller set at 0 rpm Coating and The wax dispersion was mixed together. The mixing speed was gradually increased from 700 rpm to 2000 rpm. Once 2000 rpm was reached, mixing was continued for an additional 60 seconds. The can was then placed in a tin A plated steel lid was used to close for storage. Example 11: Primary EAA Sodium Ionomer-Overvarnish Coating Preparation
[0088] 90 grams of the EAA dispersion prepared in Example 2 was dissolved in Uline (part number S-19520) The mixture was weighed into a 2 pint (0.24 liter) tin-plated steel can. 10 g of the "carnauba wax dispersion" prepared in the above was weighed into the dispersion. Col fitted with a 30mm diameter 316 SS axial impeller set at 0 rpm Coating and The wax dispersion was mixed together. The mixing speed was gradually increased from 700 rpm to 2000 rpm. Once 2000 rpm was reached, mixing was continued for an additional 60 seconds. The can was then placed in a tin A plated steel lid was used to close for storage. Example 12: Lab Coated Aluminum Panels - Michelman 4983R Color coating
[0089] 33.33" (84.66cm) x 3, 0.009" (0.02cm) thick 4" from 5.72" (90.73 cm) commercial sheet 8011 alloy aluminum Cut a piece of lab sheet measuring 10.16 cm (10.16 cm) x 38.1 cm (15 in). Use a ropane torch to remove hydrophobic contaminants and increase their surface energy Use the combustion test panel to carefully draw down the lab sheet within 24 hours of combustion. The lab sheet was placed on the template plate. A spring-loaded clip was used to draw down the lab sheet. A clean Meyer #10 rod was placed across the width of the lab sheet. Add approximately 5 mL of "Example 6" color coating to the lab sheet just before the Meyer rod. Pipette deeply. Using a smooth, even motion, slide the Meyer rod along the edge of the lab sheet. The sample was pulled lengthwise to the end. The sample was placed in a lab oven (Sheldon Ovens #SM05 89409-456) before oven curing. The lab sheet was removed and placed in the holder. The coated lab sheet and holder were placed in a 210 The dry lab sheet was placed in an oven with an air temperature of 200 °F (99.8 °C) for 60 seconds. The coated plates were then removed from the bin and cooled to ambient temperature for further testing and deep drawing performance. The lab sheets were kept.
[0090] "Coating thickness", "Sutherland friction", "Taber coating adhesion" Flat lab sheets were tested for "adhesion", "blocking" and "stickiness".
[0091] Coating thickness was measured using the ElektroPhysik Mini Test 720 (E lektroPhysik Dr.Steingroever GmbH & Co. KG, Pasteurstr. 15, 50735 Cologne, Germany) to Measure six points on a 10.16 cm x 15 inch (38.1 cm) panel It was decided by.
[0092] Sutherland friction is measured using the Sutherland Friction Tester Model 2000 (Danilee Co.,LLC,27223 Starry Mountain,S Secure the rectangle onto the rubber base pad of a 6-inch 10-cm 3 ... Cover the panel in a 15.24 cm x 2.5 cm rectangle. Made by cutting 41B weight 3M 261X wrapping film (Elec tronics Markets Materials Division 3M El ectronics 3M Center,Building 21-1 W-10,9 00 Bush Avenue St. Paul, MN 55144) and attach the piece. 41b Weight: 6 inch (15.25 cm) x 2.5 inch (6.35 cm) rectangle The panel was used to rub the sample for 500 cycles at speed setting 4. The sample was then The friction ranking scale was used to rank the samples. In all outcomes, a lower score is better than a higher score.
[0093] Taber coating adhesion test is performed by applying a coated panel to a 6 inch (15.2 5 cm (2.5 in) x 1.5 in (3.81 cm) rectangle and used for Gardco adhesive test strips. Heavy-tooth cutter (Paul N. Gardner Company Inc., 316 N .E.First Street, Pompano Beach, FL 33060) A cross-hatch pattern was cut through the coating using PA-280630 tape. (manufactured by Interpolymer and published by Paul N. Gardner Com Place a fresh strip of acrylic (sold by Pany Inc.) on the grid and place it over your finger. Smooth the tape over the crosshatch with a 100% greaseproof cloth and completely remove the tape for 60 to 120 seconds after smoothing. The tape was then quickly removed from the sample. This included a flat surface on the panel surface. The specimens were then rated using the Taber adhesion rating scale shown in Figure 7. As for the results, a lower score is better than a higher score.
[0094] The blocking test consisted of placing the coated panels into five 4-inch (10.16 cm) x 2. Cut into 5-inch (6.35 cm) rectangles, stack the rectangles on top of each other, and heat to 129°F ( Place in a preheated oven (53.89°C) and place an 11 pound (4989.52 grams) Remove the sample from the oven and store for 5 minutes. The following grading scale was used (all results lower than LTB): [Table 1]
[0095] The results are shown in Table A. [Table 2]
[0096] Using the Lab 3 draw press, a 30 mm diameter, 60 mm long shell was produced from the flat sheet. was created.
[0097] Apply a small amount of mineral oil to a clean, lint-free cloth and rub both sides of the painted seat. A light layer of lubricating mineral oil was applied to the sheet by placing it on the first draw station. A first drawshell was fabricated measuring approximately 52 mm and 29 mm in height.
[0098] If the first draw shell is acceptable, move it to the second draw station The second draw tool was placed on the shell, which was about 39 mm in diameter and 45 mm in height. We created a rule.
[0099] If the second draw shell is acceptable, it will move to the third draw station and The shell was placed in the draw tool. A third draw shell with a diameter of about 30 mm and a height of about 60 mm was placed in the draw tool. Created.
[0100] Shells with coatings that withstand drawing from flat sheets to 30x60 shapes For the coating, "top rub" and "solvent rub" tests were performed to verify the durability of the coating. Durability was assessed.
[0101] Shell top rub test is performed using the Digital Ink Rub Tester, Mode l 10-18(Testing Machines Inc.,40 McCullo 1000 1st St., New Castle, DE 19720) on a rubber-based pad. This was done by placing a worn piece of cardboard on the shell holder fixture. Place the shell in the fixture so that the top side is in contact with the cardboard and place the friction tester at rest. The rubbed shells were graded using the scale shown in Figure 8. In this ranking, a lower score is better than a higher score.
[0102] Shell Solvent Rub Test is based on 1680 Glass Packaging Institute The shells were placed in a glass jar with a te finish and very steady pressure was applied to the shells to make 70% Approximately 2 inches (5.08 cm) x 3 cm (1.2 cm) of paper is immersed in isopropyl alcohol (IPA). Rub the shells by hand with a 3-inch (7.62 cm) rectangular paper towel and cut into 30 pieces. The shells were rubbed back and forth over the entire circumference of the wheel. The rubbed shells were graded using the scale shown in Figure 9. In this ranking, a lower score is better than a higher score.
[0103] The results are shown in Table B. [Table 3] Example 13: Lab Coated Aluminum Panels - Primary EAA Color Coating
[0104] 33.33 inches (84.66 cm) of 0.009 inch thick 8011 alloy aluminum 4 inches (10.16 cm) x 35.72 inches (90.73 cm) from a commercially available sheet Cut a piece of lab sheeting measuring 15 in. (38.1 cm) x 15 in. (38.1 cm). Use a propane torch to The lab panel was then coated with a fluoride to remove hydrophobic contaminants and increase its surface energy. After the flame exposure, carefully remove the lab sheet from the drawdown plate within 24 hours. A spring-loaded clip was used to secure the lab sheet to the drawdown plate. A clean Meyer #10 rod was placed across the width of the lab sheet. Example 7: Carefully pipette the color coating onto the lab sheet just before the Meyer rod. With a smooth, even motion, pull the Meyer rod lengthwise across the lab sheet. The oven was heated in a lab oven (Sheldon Ovens #SMO5 89409-456). Before the oven cures, remove the coated lab sheet from the drawdown plate and place it in a holder. The coated lab sheet and holder were placed in an air temperature chamber at 210°F (98.9°C). The dried lab sheets were then removed from the oven and placed in an ambient temperature oven for 60 seconds. The coated lab sheets were stored for further testing and deep draw performance. .
[0105] Using the method described in Example 12, flat lab sheets were coated with Taber and then coated with Su Therland friction, coating thickness, and blocking were tested. Shown in Table C. [Table 4]
[0106] Using the Lab 3 draw press, we made a shell with a diameter of 30 mm and a length of 60 mm from the sheet. (See Example 12 for methodology.)
[0107] Shells with coatings that withstand drawing from flat sheets to 30x60 shapes For the 100% 150% 180% 190% 200% 250% 300% 350% 400% 450% 500% 600% 700% 800% 900% 1000% 1100% 1200% 1300% 1400% 1500% 1600% 1700% 1800% 1900% 2000% 2500% 3000% 4000% 5000% 6000% The durability of the coating was then measured, and the results are shown in Table D. [Table 5] Example 14: Lab Coated Aluminum Panels - Primary EAA Size and Color Coating G
[0108] 33.33" x 0.009" (0.023 cm) thick 8011 alloy aluminum from a commercially available sheet of 35.72 inches (84.66 cm) x 35.72 inches (90.73 cm) A 4 inch (10.16 cm) x 15 inch (38.1 cm) lab sheet was cut Use a propane torch to remove hydrophobic contaminants and increase their surface energy. The lab panel was exposed to a flame to remove the lab sheet. Within 24 hours of exposure to the flame, the lab sheet was carefully removed. The lab sheet was placed on the down plate using a spring-loaded clip. A clean Meyer #5 rod was placed across the width of the lab sheet. Approximately 5 mL of the size coating from Example 1 was applied to the lab sheet just before the Meyer rod. Using a smooth, even motion, the Meyer rod was carefully pipetted into the lab system. The moist, coated lab sheet and holder were then placed in a 250°F (1 The dry lab sheet was then removed from the oven and placed in a preheated oven at 21°C for 60 seconds. The mixture was then cooled to ambient temperature.
[0109] Use the spring loaded clip to drop the cured size coated lab sheet. The lab sheet was fixed on the down-down plate. A clean Meyer #10 rod was placed across the width of the lab sheet. Approximately 5 mL of the color coating from "Example 7" was placed in the lab just before the Meyer rod. Carefully pipette the mixture onto the sheet. Using a smooth, even motion, pull the Meyer rod The lab sheet was pulled in the longitudinal direction. 89409-456) before oven curing. The lab sheet was removed and placed in the holder. The coated lab sheet and holder were placed in a 210 The dry lab sheet was placed in an oven with an air temperature of 200 °F (98.9 °C) for 60 seconds. Remove from bun and allow to cool to ambient temperature.
[0110] The coated lab sheets were kept for further testing and deep drawing performance. Using the method of Taber coating, Sutherlan d Friction, coating thickness, and blocking were tested, and the results are shown in Table E. [Table 6]
[0111] Using the Lab 3 draw press, we made a shell with a diameter of 30 mm and a length of 60 mm from the sheet. (See Example 12 for methodology.)
[0112] Shells with coatings that withstand drawing from flat sheets to 30x60 shapes For the 100% 150% 180% 190% 200% 250% 300% 350% 400% 450% 500% 600% 700% 800% 900% 1000% 1100% 1200% 1300% 1400% 1500% 1600% 1700% 1 The durability of the coating was determined and the results are shown in Table F. [Table 7] Example 15: Lab Coated Aluminum Panels - Primary EAA Sizes, Colors and Overcrowds Scoring
[0113] 33.33" x 0.009" (0.023 cm) thick 8011 alloy aluminum 4 sheets of 35.72" (84.66 cm) x 35.72" (90.73 cm) A piece of lab sheet measuring 10.16 cm (10.16 cm) x 38.1 cm (15 inches) was cut. A propane torch was used to remove hydrophobic contaminants and increase their surface energy. To determine the cause of the flame exposure, the lab panel was exposed to a flame. After the flame exposure, the lab sheet was carefully removed and discarded within 24 hours. The lab sheet was placed on the down plate using a spring-loaded clip. A clean Meyer #5 rod was placed across the width of the lab sheet. Approximately 5 mL of the size coating from Example 1 was applied to the lab sheet just before the Meyer rod. Using a smooth, even motion, the Meyer rod was carefully pipetted into the lab system. The coated lab sheet and holder were then heated to 210°F (98.9°C). The dried lab sheet was then removed from the oven and placed in an oven with an air temperature of 100°C for 60 seconds. and allowed to cool to ambient temperature.
[0114] Use a spring loaded clip to hold the cured, size coated lab sheet in place. The lab sheet was fixed on a drawdown plate. A clean Meyer #10 rod was placed across the width of the lab sheet. Approximately 5 mL of the color coating from "Example 7" was placed just before the Meyer rod. Carefully pipette onto the lab sheet. Using a smooth, even motion, pipette into the Meyer The wire was pulled in the longitudinal direction of the lab sheet. Before oven curing in O5 89409-456, the coated The coated lab sheet was removed and placed in the holder. The coated lab sheet and holder were then Place in oven at 10°F (98.9°C) air temperature for 60 seconds. Removed from oven and allowed to cool to ambient temperature.
[0115] Use the spring loaded clip to attach the hardened size and color coated lab sheets The sheet was then clamped to a drawdown plate. A clean Meyer #10 rod was placed. Approximately 5 mL of the overvarnish coating of "Example 10" was carefully applied. The coating was applied directly onto the lab sheet just before the Meyer rod. Using a gentle, even motion, the Meyer rod was pulled lengthwise across the lab sheet. Oven cure in a Sheldon Oven (SMO5 89409-456) Before applying, remove the coated lab sheet from the drawdown plate and place it in the holder. The coated lab sheet and holder were then placed in an oven with an air temperature of 210°F (98.9°C). The dried lab sheet was removed from the oven and allowed to cool to ambient temperature. The coated lab sheets were kept for further testing and deep draw performance.
[0116] Using the method described in Example 12, flat lab sheets were coated with Taber and then coated with Su Therland friction, coating thickness, and blocking were tested. Shown in Table G. [Table 8]
[0117] Using the Lab 3 draw press, we made a shell with a diameter of 30 mm and a length of 60 mm from the sheet. (See Example 12 for methodology.)
[0118] For coatings that have survived pulls from flat sheets to 30x60 shells, The "top rub" and "solvent rub" tests were carried out using the method described in Example 12 to determine the coating The durability of the ring was measured, and the results are shown in Table H. [Table 9] Example 16: Lab Coated Aluminum Panels - Primary EAA Sodium Ionomer Size Size, color and overvarnish coating
[0119] 33.33" thick 8011 alloy aluminum 35.72 inch (84.66 cm) x 35.72 inch (90.73 cm) commercially available sheet Cut a 4 inch (10.16 cm) x 15 inch (38.1 cm) lab sheet from the paper. A propane torch was used to remove hydrophobic contaminants and increase their surface energy. The lab panel was exposed to a flame to confirm the presence of the lab sheet. Within 24 hours of exposure to the flame, the lab sheet was carefully removed. The lab sheet was placed on the drawdown plate using a spring-loaded clip. The lab sheet was fixed to a lowering plate. A clean Meyer #5 rod was placed across the width of the lab sheet. Approximately 5 mL of the size coating from "Example 2" was placed on the lab bench just before the Meyer rod. Using a smooth, even motion, the Meyer rod was carefully pipetted into the lath. The coated lab sheet and holder were then placed in a 210°F (98. The dry lab sheet was then placed in an oven at an air temperature of 150°C (47°F) for 60 seconds. The dry lab sheet was then removed from the oven and placed in a 150°C (47°F) oven. The mixture was then cooled to ambient temperature.
[0120] Use spring loaded clips to hold hardened, size coated lab sheets The lab sheet was fixed onto the drawdown plate. A clean Meyer #10 rod was placed across the width of the lab sheet. Approximately 5 mL of the color coating from "Example 8" was placed just before the Meyer rod. Using a smooth, even motion, pipette the Meyer The wire was pulled in the longitudinal direction of the lab sheet. Before oven curing in O5 89409-456, the coated The coated lab sheet was removed and placed in the holder. The coated lab sheet and holder were then Place in oven at 10°F (98.9°C) air temperature for 60 seconds. Remove from oven and allow to cool to ambient temperature.
[0121] Spring loaded clips are used to attach hardened size and color coated lasers The lab sheet was fixed to the drawdown plate. A clean Meyer Carefully apply approximately 5 mL of overvarnish coating of "Example 11" to the Pipette onto the lab sheet just before the Mayer rod. Using a smooth, even motion The Meyer rod was pulled lengthwise across the lab sheet. Before oven curing in a drawdown oven (Oven #SMO5 89409-456), The coated lab sheet was removed from the plate and placed in the holder. The holder was then placed in an oven with an air temperature of 210°F (98.9°C) for 60 seconds. The coated lab sheets were removed from the oven and allowed to cool to ambient temperature. Further Testing and Deep Drawing The coated lab sheets were kept for performance purposes.
[0122] Using the method described in Example 12, flat lab sheets were coated with Taber and then coated with Su Therland friction, coating thickness, and blocking were tested. As shown in Table I. [Table 10]
[0123] Using the Lab 3 draw press, we made a shell with a diameter of 30 mm and a length of 60 mm from the sheet. (See Example 12 for methodology.)
[0124] For coatings that have survived pulls from flat sheets to 30x60 shells, The "top rub" and "solvent rub" tests were carried out using the method described in Example 12 to determine the coating The durability of the ring was measured, and the results are shown in Table J. [Table 11] Example 17: Curing Results - Time and Temperature
[0125] A base coating (see Example 5) on the base, a color coating (see Example 8), and Tolerance required for curing the overvarnish coating on the color (see Example 11) An array (see Table K) was designed to determine the optimal time and temperature for size coating. The coating is the same as in Example 16, except that it is replaced by a base coating. The coating was applied to the panel using the same method as in Example 1. [Table 12]
[0126] The lab panel was coated with the base and the panel start temperature, dwell time and panel temperature listed in the array were The base coated samples were cooled and the color coating was applied. The coating is then overcoated with acrylic and then cured using the same cure temperatures and times as listed in Table K. The color coated samples were cooled and overcoated with an overvarnish and the results shown in Table K were The flat panels were then cured using the same cure temperatures and times listed in . Coating thickness, Sutherland friction, Taber coating adhesion and blocking The coating performance was evaluated using the method described in Example 12. The results are shown in Table L. [Table 13]
[0127] All coated panels with minimally acceptable cured coating properties were then subjected to a 3-draw roller press ( The mixture was then drawn into a shell measuring 30 mm in diameter and 60 mm in height using the method described in Example 12. The shells having the coating which survived the drawing process were then subjected to the method described in Example 12. The results of these tests are shown in Table M. show. [Table 14] Example 18: Coating Chemistry Process Results
[0128] Table N shows the dispersion particle size, ionomer cation type, percent ionomerization, and acrylonitrile. How does the acrylic acid to ethylene ratio and wax content change the final coating performance? Shows. [Table 15]
[0129] Mix Sunspers Blue 15:3 pigment dispersion with the appropriate amount of EAA dispersion. 24 test coats were prepared by mixing pigments at 51 percent EAA solids. Color coatings were made from each of the 700r rings. Cole-P fitted with a 30mm diameter 316SS axial impeller set at pm By mixing with the Armer mixer (Model #50006-01), e (Part No. S-19520) 1 / 2 pint (0.24 liter) tin-plated steel can The mixing speed was gradually increased from 700 rpm to 2000 rpm. Once 2000 rpm was reached, mixing was continued for an additional 60 seconds. The can was then transferred to a tin-plated steel The container was closed for storage using a stainless steel lid.
[0130] Coated lab panels were prepared and heated in air at 210F (98.89C) for 60 seconds. The flat panels were then coated with a Taber coating using the method described in Example 12. Adhesion, Sutherland friction, coating thickness, and blocking performance were tested. The results are shown in Table O. [Table 16]
[0131] The coated flat metal for each test was drawn using the method described in Example 12 to a length of 30 mm The shells were then cut into 60 mm diameter x 60 mm height shells. The shells with coatings that withstood the tensile test were then cut into 60 mm diameter x 60 mm height shells. The wells were tested for "top rub" and "solvent rub" performance using the method described in Example 12. The results of these tests are shown in Table P. [Table 17] Example 19: Commercially available roll coated aluminum panels - primary EAA sodium ionomer - Base / Colour / Overvarnish and interior lacquer coatings
[0132] Primary sodium EAA ionomers prepared in a 60 gallon (227.1 liter) reactor. Each coating (white background) was prepared using the same formula as used to prepare Example 2. The company produced 5 gallons (18.9 liters) of "White Base, Color, and Overvarnish." The "Base Coating" is 37.9 pounds (17.2 kilograms) of primary EAA sodium. 2.1 pounds (953 grams) of "Sunsperse White 6" on Muonomer " is added with stirring and mixed into a homogenous composition, then passed through a 150 micron bag. The solution was prepared by filtering the solution into a plastic 5 gallon (18.9 liter) pail. The "color coating" is 34.6 pounds (15.7 kilograms) of primary EAA sodium. Add 5.4 pounds (2.4 kilograms) of Sunspers to the ionomer while stirring. "E Blue 15:3" was added and mixed to a homogenous composition, then 150 micron ballast was added. by filtering through a filter into a plastic 5-gallon (18.9 liter) pail. The "over varnish" was prepared by mixing 4.2 pounds (1.9 kilograms) of carnauba wax. 35.8 lbs (16.2 kg) of sucrose dispersion (the same formulation used to make Example 9) was added to the Add to the primary EAA sodium ionomer (program) with stirring until a homogenous composition is formed. The mixture was then passed through a 150 micron bag into a plastic 5 gallon (18.9 liter) container. The mixture was adjusted by filtering into a 300 ml can.
[0133] 35.7" (90.68 cm) x 33" (0.009 cm) thick Able to handle 0.3 inch (84.58 cm) flat 8011 aluminum sheet A commercially available direct roll coater was set up with a diameter of 1.5 mm rotating at 72 rpm. 60 / min using a 12-inch (30.48 cm) urethane coating applicator roller The coater was operated on the sheet. Immediately after the coating was applied to the sheet, it was dried. in a Wagner Litho oven with the time / temperature profile shown in FIG. An EAA film was formed.
[0134] The first coating applied was a white base. The coating was then cured in a transfer oven, and the base coating was returned to its original orientation and sent back to the coater feed system. The body base coating is removed from the roll coater system and the system is washed with water. The base-coated sheet was then coated with the color coating. The cured sheet was overcoated with a coating and cured using the same oven curve. Return it to the coater supply without reversing again to purge the system from the liquid color coat. Then, it was washed with water and primed with overvarnish (used as an interior lacquer). The "coater" is applied to the bare metal (exposed metal surface) and cured using the same oven curve, and the final For overvarnishing, the plate was returned to the coater feed without being turned over. Since the overvarnish coating and overcoat coating were the same, No purging or cleaning of the system was required in between. The overvarnished samples were It has the same oven curve to complete the metal coating for screw cap production The cured material was then fed through a curing oven.
[0135] Approximately 500 fully coated sheets were stacked on pallets and shipped to the warehouse for further processing. The bottles were transported by truck to a commercial screw cap manufacturing facility. A block test was set up, which consisted of placing temperature sensors on 500 pallets and measuring the temperature for 5 00 sheets on a standard 900 pound (408.2 kg) commercially available pallet The pallets were then stored in a storage facility. It remains there for days, with temperatures ranging from 70°F (21.11°C) to 110°F (43.33°C). Four days later, the 900-pound pallet was removed and replaced by a 500-pound pallet. The sheets were inspected for blocking and none of the sheets showed blocking.
[0136] Prior to running the sheet on a commercial screw cap molding line, the sheet was Using the method, the flat coated metal was coated with Taber Coating Adhesion, Sutherl and friction, coating thickness and blocking were tested. The results are shown in Table Q below. show. [Table 18]
[0137] The flat sheets were tested and then run through a commercial production line to make screw caps. The caps were then evaluated for "top rub" and "solvent rub" performance using the method described in Example 12. The results of these tests are shown in Table R. [Table 19]
[0138] The caps were fitted to the bottles with a standard GPI 1680 finish.
[0139] The cap is an Andre Zalkin Model TM3, single head kit. Capper(5 Route Andre Zalkin,27390 Montreui The capper was made of Zalk in 30×60 Stelvin type capper head installed, industry standard top Prode, thread roller, thread roller force, open bottle roller, open bottle roller The capped samples were then set up using the Force and modified settings for 24 hours. Leave it and then use Torqo II (Mesa Labs, 12100 West 6th The slip torque and breaking torque were measured using the The results are shown in Table S. [Table 20]
[0140] After removing the cap, visually inspect the inner lacquer to ensure proper cap installation and capping. It was determined whether the cap removal process damaged the coating. No disappearance was observed.
[0141] The various embodiments described above are provided by way of illustration only and are not intended to be limiting of the invention as claimed. The present invention should not be construed as limiting the scope of the present invention. The present invention is not limited to the above exemplary embodiments and applications, and is not intended to be limited to the true spirit and scope of the invention as set forth in the claims. and various modifications that may be made to the claimed invention without departing from its scope. Modifications and variations will be readily apparent and are set forth in the following claims.
Claims
1. A method for producing a screw cap closure, comprising the steps of: mixing an ethylene acrylic acid copolymer with water and a base to obtain a mixture in which the ethylene acrylic acid copolymer is present in a concentration of 15 to 45 weight percent, the base neutralizing 25 to 100 mole percent of the acrylic acid functionality; heating the mixture with stirring to produce a dispersion; applying the dispersion to a metal to form a coating layer on the metal; deep drawing said coating layer and said metal to form said screw cap closure.
2. 2. The method of claim 1, wherein the mixture is heated to 110°C.
3. 10. The method of claim 1 further comprising adding a pigment to said mixture.
4. 10. The method of claim 1 further comprising adding a wax to said mixture.
5. 2. The method of claim 1, wherein the ethylene acrylic acid copolymer comprises an acrylic acid content of about 20.5 percent.
6. 2. The method of claim 1, wherein the base comprises at least one of ammonium hydroxide or sodium hydroxide.
7. 7. The method of claim 6, wherein said base comprises ammonium hydroxide and sodium hydroxide, said ammonium hydroxide neutralizing about 30 mole percent of said acrylic acid functional groups and said sodium hydroxide neutralizing about 40 mole percent of said acrylic acid functional groups.
8. A method for producing a screw cap closure, comprising the steps of: coating a metal substrate with a first coating composition, said first coating composition comprising 15 to 45 weight percent of an ethylene acrylic acid copolymer in an aqueous dispersion having 25 to 100 mole percent of neutralized acrylic acid functionality; curing the first coating composition on the metal substrate by heating the metal substrate to a temperature of about 150° F. (65.6° C.) to about 250° F. (121° C.) to form a first coating layer; deep drawing said first coating layer and said metal substrate to form said screw cap closure; A method comprising:
9. 10. The method of claim 8, further comprising coating the metal substrate with a second coating composition, the second coating composition comprising 15 to 45 weight percent of an ethylene acrylic acid copolymer in an aqueous dispersion having 25 to 100 mole percent of the acrylic acid functionality neutralized, and a pigment.
10. 10. The method of claim 8, further comprising coating the metal substrate with a third coating composition, the third coating composition comprising 15 to 45 weight percent of an ethylene acrylic acid copolymer in an aqueous dispersion having 25 to 100 mole percent of the acrylic acid functionality neutralized, and a wax.
11. 10. The method of claim 8, wherein the first coating composition is free of volatile organic compounds (VOCs).
12. 10. The method of claim 8, wherein the first coating composition is intentionally free of BPA.
13. 2. The method of claim 1, wherein the coating layer on the metal is cured by heating the metal to a temperature of from about 150°F (65.6°C) to about 250°F (121°C).
14. A method for producing a screw cap closure, comprising the steps of: Obtaining a coated substrate produced by coating a metal substrate with a coating composition, said coating composition comprising 15 to 45 weight percent of an ethylene acrylic acid copolymer in an aqueous dispersion having 25 to 100 mole percent of neutralized acrylic acid functionality; deep drawing the coated substrate to form the screw cap closure; A method comprising:
15. 15. The method of claim 14, wherein the coating composition is cured by heating the coated substrate to a temperature of from about 150°F (65.6°C) to about 250°F (121°C).
16. 15. The method of claim 14, wherein deep drawing the coated substrate includes shaping the coated substrate to a diameter of about 30 mm and a length of about 60 mm.
Citation Information
Patent Citations
Aqueous dispersion of ethylene copolymer
JP1987141046A
Method for preparing aqueous dispersions of ethylene / α,β-unsaturated carboxylic acid interpolymers
JP1993505644A
Production of aqueous ethylene / acrylic acid copolymer resin dispersion
JP1997278897A
Coating composition containing low mfi ethylene acrylic acid copolymer
JP2003529624A
Aqueous dispersion composition
JP2010043186A